Race pace interval swimming: effect of rest interval on physiological and technical parameters and correlation with handgrip strength in boys and girls swimmers - Theofilidis, G.; Machos, C.; Karatrantou, K.; Toubekis, A.; Karampina, E.; Gerodimos, V. (Inquiries in Sport & Physical Education, 2019)
The aim of the present study was to examine the effect of continuous and intermittent race pace 200-m front crawl in overall performance, physiological and technical parameters. The correlation of maximum handgrip strength and handgrip strength endurance with performance and technical parameters during 200-m front crawl swimming performed continuously or in 4 x 50 splits with different rest intervals was also examined. Sixteen swimmers (girls, n= 8, boys, n = 8, age: 13.8 ± 1.1 years) participated in the study. Swimmers conducted three front crawl swim tests at 200-m maximum speed (race pace): i. continuous 200-m (200T), ii. 4?50-m with 5 s rest between each 50-m lap (4x50-R5) and iii. 4?50-m with 10 s rest between each 50-m lap (4x50-R10). Lactate and heart rate (HR) were measured post-exercise. Stroke length, stroke rate, stroke index, and swimming speed were calculated in each condition. Maximum isometric handgrip strength and strength endurance were tested in the following day. Boys were faster than girls in all conditions (main effect of gender p=0.015). Moreover, swimming speed was higher in 4x50-R10 compared to the other two conditions (p<0.001). Blood lactate and post-exercise heart rate were no different between conditions and genders (p>0.05). Stroke length was no different between conditions and genders (p>0.05), while stroke rate was increased in 4x50-R5 and 4x50-R10 conditions compared to 200T (p<0.001), and a significant "condition" x "gender" interaction was observed (p=0.028). Stroke index was increased in 4x50-R5 and 4x50-R10 conditions compared to 200T (p<0.001) and was higher in boys (p<0.05). Maximum handgrip strength of the preferred hand was correlated with SL, SI and speed only in the whole group (r=0.61 and r=0.73 respectively) and in the boys` group (r=0.74 and r=0.88 respectively) (p<0.05). In conclusion, during a maximum intensity swimming at 200-m race pace, a rest interval up to 10 s between laps does not differentiate physiological parameters but affects technical parameters. Maximum handgrip strength but not strength endurance correlates with overall performance.